Design Thinking as a Tool for Interdisciplinary Education in Health Care. (September 2016) - van de Grift, Tim C.; Kroeze, Renske
Abstract : Problem: Grappling with complex structural health care issues requires medical professionals to have training in skills and knowledge that go beyond the basic and clinical sciences. It is also crucial for health care professionals to be able to work collaboratively. However, medical education has only limitedly institutionalized the teaching of these skills. Approach: In fall 2014, a one-semester crossover course called Hacking Healthcare was developed by the University of Amsterdam in cooperation with the Gerrit Rietveld Academie of Fine Arts and six health care institutions in the greater Amsterdam area. The course comprised one or two weekly three-hour evening sessions consisting of a lecture, workshop, and group work. It was structured using the three stages of the design thinking process—inspiration, ideation, and implementation. Twenty-seven medicine, psychology, other science disciplines, and art students participated, working in interdisciplinary groups on an assigned case study. Outcomes: The course yielded both unconventional and holistic key insights and a wide range of tangible outcomes, which were also considered to be relevant by the patient. Among university (i.e., nonart) students (n = 14), the average overall score of the course was 8.5 out of 10, with 10 being the highest rating. Aspects of the course that were mentioned as positive points were the activating teaching environment, academic development, and development of collaboration skills and creative capabilities. Next Steps: This approach could be applied in other fields, such as medical education on a larger scale, clinical practice, and the design of scientific research.